Development Challenges and Solutions After the Arab Spring
XIII, 243 p.
Keywords: Since the events of 2011, most Arab countries have slipped into a state of war, and living conditions for the majority of the working population have not changed for the better. This edited collection examines the socioeconomic conditions and contests the received policy framework to demonstrate that workable alternatives do exist.